2023
DOI: 10.3390/microorganisms11082002
|View full text |Cite
|
Sign up to set email alerts
|

Different Responses of Bacteria and Archaea to Environmental Variables in Brines of the Mahai Potash Mine, Qinghai-Tibet Plateau

Abstract: Salt mines feature both autochthonous and allochthonous microbial communities introduced by industrialization. It is important to generate the information on the diversity of the microbial communities present in the salt mines and how they are shaped by the environment representing ecological diversification. Brine from Mahai potash mine (Qianghai, China), an extreme hypersaline environment, is used to produce potash salts for hundreds of millions of people. However, halophiles preserved in this niche during d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…Similarly, Loubna et al isolated and identified more archaea in the Great Salt Lake, which has significant salinity differences between the northern and southern regions [30]. Xie et al also demonstrated that the diversity and composition of archaea in the brines of the Mahai potash mine on the Tibetan Plateau are mainly influenced by the chemical properties of the hypersaline water [31]. While unique microbial community distributions do exist, our study suggests that salinity is the primary driver of species composition differences in lake ecosystems, whereas other factors such as pH, nutrition, and temperature usually occupy the second place in microbial community construction [13,29,32].…”
Section: The Microbial Community and Dominant Groups In Xt And Dtmentioning
confidence: 98%
“…Similarly, Loubna et al isolated and identified more archaea in the Great Salt Lake, which has significant salinity differences between the northern and southern regions [30]. Xie et al also demonstrated that the diversity and composition of archaea in the brines of the Mahai potash mine on the Tibetan Plateau are mainly influenced by the chemical properties of the hypersaline water [31]. While unique microbial community distributions do exist, our study suggests that salinity is the primary driver of species composition differences in lake ecosystems, whereas other factors such as pH, nutrition, and temperature usually occupy the second place in microbial community construction [13,29,32].…”
Section: The Microbial Community and Dominant Groups In Xt And Dtmentioning
confidence: 98%